2013
DOI: 10.1155/2013/236374
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Multimodal Therapy to Standard Management of Steady State Sickle Cell Disease

Abstract: Most people on folic acid to boost erythropoiesis and prophylactic antimicrobials, the standard management of steady state sickle cell disease (SCD), have unacceptable numbers of crises. The objective of this study was to evaluate the effects of adding multimodal therapy with potassium thiocyanate and omega-3 fatty acids to the standard management of steady state SCD. Pre- and post-treatment numbers of crises and other disease indices were compared in 16 HbSS individuals on folic acid and paludrine after 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These findings indicated the important role of fatty acid abnormality in the chronic inflammatory state associated with the disease [14,15]. In addition, our group and others have shown that supplementing SCD patients with omega-3 fatty acids corrects cell membrane abnormalities and confer protection against vaso-occlusive pain episodes, severe anaemia and oxidative stress [16][17][18][19], and improves red blood cells flexibility in mice [20]. However, little is known about the potential antiinflammatory role of n−3 fatty acids in SCD.…”
Section: Introductionmentioning
confidence: 69%
“…These findings indicated the important role of fatty acid abnormality in the chronic inflammatory state associated with the disease [14,15]. In addition, our group and others have shown that supplementing SCD patients with omega-3 fatty acids corrects cell membrane abnormalities and confer protection against vaso-occlusive pain episodes, severe anaemia and oxidative stress [16][17][18][19], and improves red blood cells flexibility in mice [20]. However, little is known about the potential antiinflammatory role of n−3 fatty acids in SCD.…”
Section: Introductionmentioning
confidence: 69%
“…1,12,13 Given the complex nature of SCD pathophysiology, a multimodal therapy or a single drug with multiple mechanisms of action may be necessary to achieve clinical effectiveness. 14,15 The multiple biological and pleiotropic effects of the v-3 fatty acid docosahexaenoic acid (DHA, 22:6v3) that include, but are not limited to, its antioxidant, anti-inflammatory, antiadhesion, anti-aggregation properties and its positive effects on erythrocyte rheology and vasodilatation [16][17][18][19][20][21][22][23][24][25] all offer potential therapeutic benefits in SCD. In addition, resolvins, endogenous lipid mediators generated from DHA and eicosapentaenoic acid (EPA; 20:5v3), have been shown to increase nitric oxide availability and reduce inflammatory pain.…”
Section: Introductionmentioning
confidence: 99%
“…20,[27][28][29] Treatment of patients with SCD with the v-3 fatty acids DHA and EPA has been shown to correct cell membrane fatty acid balance and confer protection against vaso-occlusive pain episodes, hemolysis, oxidative stress, and inflammation. [16][17][18][19][20][21] Treatment of mouse models of SCD with DHA and EPA also improves erythrocyte flexibility and reduces vascular endothelial activation and sickle cell-related end-organ injury. 30,31 SC411 is a novel DHA ethyl ester formulation with a proprietary delivery platform (Advanced Lipid Technology, or ALT) that enhances DHA bioavailability and overcomes the variable absorption related to dietary fat ("food effect") 32,33 To investigate the safety and efficacy of 3 dose levels of SC411 in children with SCD, the phase 2 SCOT (Sickle Cell Omega-3 Treatment) trial (NCT02973360) was conducted at 11 sites in the United States.…”
Section: Introductionmentioning
confidence: 99%